2006
DOI: 10.1002/ajp.20207
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite markers for standardized genetic management of captive colonies of rhesus macaques (Macaca mulatta)

Abstract: To preserve genetic variability and minimize genetic subdivision among captive Macaca mulatta at each of the U.S. National Institutes of Health (NIH)-sponsored regional research colonies, the genetic structure of each colony must be characterized. To compare population genetic and demographic parameters across colonies and generations, one standard panel of highly informative genetic markers is required. We assembled a core marker set of four multiplex polymerase chain reaction (PCR) panels comprising 15 autos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 17 publications
2
33
0
Order By: Relevance
“…This deviation and the variations in heterozygosity levels may be explained by the facts that macaques from a structured population were sampled and artificially treated as a randomly mating population. In our study, the PIC of 10 screened loci ranged from 0.52 to 0.82, with an average of 0.70 for 10 highly polymorphic loci and an average of 0.73 for 7 most polymorphic loci, which approximate the estimate of PIC (0.74) across 15 loci from blood samples (Kanthaswamy et al 2006). Because the frequency of heterozygotes at a particular locus is strongly correlated with the estimate of its PIC value, microsatellites with higher PIC value are especially useful for genetically characterizing a given individuals (Ude et al 2003).…”
Section: Screening Of Microsatellite Loci With Fecal Dnasupporting
confidence: 49%
See 1 more Smart Citation
“…This deviation and the variations in heterozygosity levels may be explained by the facts that macaques from a structured population were sampled and artificially treated as a randomly mating population. In our study, the PIC of 10 screened loci ranged from 0.52 to 0.82, with an average of 0.70 for 10 highly polymorphic loci and an average of 0.73 for 7 most polymorphic loci, which approximate the estimate of PIC (0.74) across 15 loci from blood samples (Kanthaswamy et al 2006). Because the frequency of heterozygotes at a particular locus is strongly correlated with the estimate of its PIC value, microsatellites with higher PIC value are especially useful for genetically characterizing a given individuals (Ude et al 2003).…”
Section: Screening Of Microsatellite Loci With Fecal Dnasupporting
confidence: 49%
“…In total, 18 microsatellite markers (D12S372, D9S934, D16S403, D1S548, D3S1768, D5S820, D6S311, D5S1457, D6S2741, D14S306, D3S3045, D21S1246, D6S2419, D7S513, D4S1645, D15S644, D12S67, and D18S536) were chosen as the candidate loci based on previous genetic studies of macaques, which amplified these loci from blood or tissue samples (Kanthaswamy and Smith 1998, Kanthaswamy et al 2006, Li et al 2009 (Table 1).…”
Section: Microsatellite Loci Screening and Sequence Analysismentioning
confidence: 99%
“…Investigations by Andrade et al (2004), Doxiadis et al (2003Doxiadis et al ( , 2006, Ferguson et al (2007), Hernandez et al (2007), Smith (1998, 2004), Kanthaswamy et al (2006), Malhi et al (2007), Morin et al (1997), Penedo et al (2005), Satkoski et al (2007), and Viray et al (2001) have all characterized the genetic composition of rhesus macaque populations in the wild and in captivity. Most of these studies have reported discrete genetic differences between Indian and Chinese rhesus macaques and much greater genetic heterogeneity and substructuring in the latter than in the former.…”
Section: Introductionmentioning
confidence: 99%
“…D3S1768 locus was highly polymorphic and 24 alleles were detected. D1S548 and D3S1768 were found to be polymorphic in rhesus macaques, M. mulatta (Kanthaswamy et al 2006). Additionally the results obtained by Chu et al (1999) in Taiwanese macaques, M. cyclopis, Nurnberg et al (1998) in rhesus macaques and Goossens et al (2000) in chimpanzees, Pan troglodytes troglodytes demonstrated that D1S548 locus was polymorphic.…”
Section: Resultsmentioning
confidence: 74%